Impacto no apreçamento de derivativo pelo conhecimento prévio do calendário de divulgação de resultados - Poletti, Fernando de Castro (2015)
From the study of an econometric work about the impact of information on the return of an asset, we proposed a simplification of the model in order to analyze an specific event with well-defined schedule, quarterly financial results. For some companies, we found evidence that the model matches the data and we then priced call and put options using the Monte Carlo method. We obtained significant differences in the mark to market for the options concerning the proposed model when compared to the black-scholes one and, by performing the backtest on the sample using delta-hedge strategies, we got improved results for some scenarios.